2018
DOI: 10.1155/2018/6780494
|View full text |Cite
|
Sign up to set email alerts
|

Patient with Marfan Syndrome and a Novel Variant in FBN1 Presenting with Bilateral Popliteal Artery Aneurysm

Abstract: We present a 43-year-old man with aortic root dilation, mitral valve prolapse, and marfanoid appearance, who presented with acute onset left leg pain. He underwent a Doppler ultrasound that revealed left popliteal artery aneurysm with thrombus. CT angiogram showed bilateral popliteal artery aneurysms. After repairing of his left popliteal artery aneurysm, he was sent for genetic evaluation. He was diagnosed with Marfan syndrome (MFS) based on the revised Ghent criteria and then underwent FBN1 sequencing and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Gaertner et al (15) screened 15 patients with FBN1 mutations and they detected peripheral aneurysms in 10 of these patients, but none of them appeared in the internal mammary arteries. Bilateral popliteal aneurysms in a patient with a novel FBN1 mutation were reported by Mohammad et al(16), and Ghonem et al(17) described a left subclavian artery aneurysm in a genetically confirmed MFS patient.…”
mentioning
confidence: 76%
“…Gaertner et al (15) screened 15 patients with FBN1 mutations and they detected peripheral aneurysms in 10 of these patients, but none of them appeared in the internal mammary arteries. Bilateral popliteal aneurysms in a patient with a novel FBN1 mutation were reported by Mohammad et al(16), and Ghonem et al(17) described a left subclavian artery aneurysm in a genetically confirmed MFS patient.…”
mentioning
confidence: 76%
“…We found reports of aneurysmal dilatations in other segments of the aorta, in visceral branches, pulmonary arteries, and peripheral arteries in patient with MFS, but few reports relating the syndrome to PAAs. [7][8][9][17][18][19] Yetman et al 17 conducted a study with 140 MFS patients over the age of 18. CT or MRI images were acquired from the base of the skull to the bifurcation of the iliac arteries.…”
Section: Marfan Syndromementioning
confidence: 99%
“…4,5 Development of PAAs in patients with Marfan Syndrome (MFS) is rare, and few cases have been reported. [7][8][9] Gaertner et al 10 identified one patient with a PAA among 15 MFS patients who underwent vascular examination using ultrasound.…”
Section: Introductionmentioning
confidence: 99%